Answer:
Option B
Step-by-step explanation:
We can see that, from the picture provided, the graphs intersect at points( 0, 4 ) and ( - 4, 4 ), respective to functions f( x ) and g( x ). These intersection points makes each function equivalent to one another, and hence -
Function f( x ) where x = - 4 / Function g( x ) where x = - 4,
[tex]f( - 4 ) = 4,\\g( - 4 ) = 4\\----------\\f ( - 4 ) = g ( - 4 )[/tex]
Respectively function f( x ) where x = 0 / Function g( x ) where x = 0,
[tex]f( 0 ) = 4,\\g( 0 ) = 4\\----------\\f ( 0 ) = g ( 0 )[/tex]
Your solution should be option b, " f(-4) = g(-4) and f(0) = g(0) "